A Randomized Study Evaluating Cinacalcet to Treat Hypercalcemia in Renal Transplant Recipients With Persistent Hyperparathyroidism. Issue 11 (15th September 2014) - Evenepoel, P.; Cooper, K.; Holdaas, H.; Messa, P.; Mourad, G.; Olgaard, K.; Rutkowski, B.; Schaefer, H.; Deng, H.; Torregrosa, J. V.; Wuthrich, R. P.; Yue, S.
<x xml:space="preserve">Abstract</x> Persistent hyperparathyroidism (HPT) after kidney transplantation (KTx) is associated with hypercalcemia, hypophosphatemia and abnormally high levels of parathyroid hormone (PTH). In this randomized trial, cinacalcet was compared to placebo for the treatment of hypercalcemia in adult patients with persistent HPT after KTx. Subjects were randomized 1:1 to cinacalcet or placebo with randomization stratified by baseline corrected total serum calcium levels (≤11.2 mg/dL [2.80 mmol/L] or >11.2 mg/dL [2.80 mmol/L]). The primary end point was achievement of a mean corrected total serum calcium value <10.2 mg/dL (2.55 mmol/L) during the efficacy period. The two key secondary end points were percent change in bone mineral density (BMD) at the femoral neck and absolute change in phosphorus; 78.9% cinacalcet‐ versus 3.5% placebo‐treated subjects achieved the primary end point with a difference of 75.4% (95% confidence interval [CI]: 63.8, 87.1), p < 0.001. There was no statistical difference in the percent change in BMD at the femoral neck between cinacalcet and placebo groups, p = 0.266. The difference in the change in phosphorus between the two arms was 0.45 mg/dL (95% CI: 0.26, 0.64), p < 0.001 (nominal). No new safety signals were detected. In conclusion, hypercalcemia and hypophosphatemia were effectively corrected after treatment with cinacalcet in patients with persistent HPT after KTx.